Prison Letters of St. Ap. Paul – Theories about the Place of Writing - Boev, Georgi (Forum Theologicum Sardicense, 2025)
Georgi Boev, Prison Letters of St. Ap. Paul – Theories about the Place of Writing. The current paper examines three different theories regarding the city where Paul wrote his letters while in prison. The letters in question are Ephesians, Philippians, Colossians, and Philemon. Contemporary Biblical scholars propose three main theories about the location of Paul's imprisonment. The most widely accepted theory, particularly among Orthodox scholars, is that Paul was in Rome during his first trial. The second theory suggests Caesarea in Palestine, while the third theory posits that Paul was in Ephesus. In the introductory section of the paper, I present some explicit and implicit internal evidence for categorizing these four letters as “prison letters.” I then introduce and analyze the three main theories regarding the place of their composition. Each theory is compared based on its arguments, followed by a critical evaluation and discussion of the challenges associated with each theory.